2019
DOI: 10.1177/000313481908500953
|View full text |Cite
|
Sign up to set email alerts
|

Human Acellular Dermal Matrix is a Viable Alternative to Autologous Skin Graft in Patients with Cutaneous Malignancy

Abstract: Skin substitutes have shown success in complex wound reconstruction. We evaluate the use of a human acellular dermal matrix (ADM) as a viable alternative to autologous skin grafting for defects secondary to skin cancer excision. An institutional review board–approved, retrospective review of ADM-reconstructed defects secondary to skin cancer excision between 2012 and 2018 was conducted. ADM was indicated in patients with preclusive factors for general anesthesia, protracted procedure time, reluctance for addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In recent years, ADM graft combined with ultrathin STSG is a common technique in complex wounds of hand hot-crush injuries. The efficacy and advantages of ADM have been well documented [ 6 9 , 18 , 19 ]. This technique allows for neovascularised tissue to form overexposed or denuded structures within these wounds, creating a more robust vascularised tissue bed for neovascularisation of subsequently placed skin grafts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, ADM graft combined with ultrathin STSG is a common technique in complex wounds of hand hot-crush injuries. The efficacy and advantages of ADM have been well documented [ 6 9 , 18 , 19 ]. This technique allows for neovascularised tissue to form overexposed or denuded structures within these wounds, creating a more robust vascularised tissue bed for neovascularisation of subsequently placed skin grafts [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Some authors reported that ADM was used for the reconstruction of defects secondary to skin cancer excision with no donor site morbidity; the median interval to complete wound healing was 42 days, and the rate of graft failure was 2.6%. 21 Pan et al used composite graft with ADM to treat 19 cases of burn or scar wounds and reported a satisfactory long-term follow-up appearance of the skin donor site. 22 Li et al retrospectively evaluated the outcomes of the co-grafting ADM with autologous thin split-thickness skin for the wound coverage in burn patients and identified acceptable aesthetic outcomes and less scar hyperplasia at the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Produced from human or animal skin, ADM is favorable for full-thickness skin wound healing and can reduce scar tissue formation [21,[30][31][32]. After transplantation in the wound bed, ADM enhances the synthesis of hyaluronic acid and induces wound angiogenesis [29,33,34].…”
Section: Acellular Dermal Matrix (Adm)mentioning
confidence: 99%